Optimization of diagnostic and treatment algorhythm of blunt thoracic traumas in patienrs with combined thoracic and brain trauma. - A. B. Kytovyi; V. V. Pymakhov (Medičnì Perspektivi)
Results of treatment of 71 victims with combined blunt thoracic and brain trauma were analysed. In the main group (n=35) there was used algorithm, envisaging videothoracoscopic interventions and widening indications for chest stabilization. Mentioned above technique enabled to increase efficiency of diagnostic and treatment in patients with mild and moderately severe brain trauma; this was reflected both in acceleration of restoration of respiratory index by 5,8 days, consciousness – by 4,3-4,9 days depending on trauma severity and decrease of postoperative complications and lethality number.